THE IMPACT OF HALAL LABEL IN HALAL FOOD BUYING DECISIONS - Millatina, Afifah Nur; Hakimi, Fifi; Budiantoro, Risanda Alirastra; Arifandi, Muhammad Rizky (Universitas Muhammadiyah Surakarta, 2022)
The current development of the halal industry has experienced a very significant increase to attract the attention of various groups. Trend indicators from the halal business can be seen in seven industrial sectors that continue to show an increase, including Islamic financial services, Halal food and beverages, Halal tourism, fashion, halal media and recreation, and halal pharmaceuticals and cosmetics. This study aims to raise the importance of awareness of halal label on halal food and beverages in Indonesia. The quantitative research method used in this research is to apply Partial Least Square-Structural Equation Modeling (PLS-SEM) through Smart-PLS software. The sample of this research is 100, with the sampling technique used being non-probability sampling with the purposive sampling method. The results of this study are the significant influence of the halal label variable on purchase intention, purchase intention on buying decision, and the halal label variable on buying decision on halal food products in Indonesia. Alternatively, on product packaging, awareness of halal Indonesian society has begun to increase and make halal a lifestyle.